Levosimendan Hemodynamic Effects Depending on the Outcome of Sepsis - I. N. Tyurin; D. N. Protsenko; I. A. Kozlov (Вестник анестезиологии и реаниматологии)
The objective: to study hemodynamic and clinical effects of levosimendan depending on the clinical outcome in patients with sepsis and impaired cardiac pumping function.Subjects and Methods. the retrospective study involved 31 patients of 52.7 ± 2.8 years old with sepsis or septic shock which were treated with levosimendan at the dose of 0.16 [0.15‒0.17] mg/kg (0.11 [0.1‒0.12] μg × kg-1 × min-1) on days 1–4 of ICU stay. The patients were divided into the following groups: Group 1 ‒ survivors (n = 19) and Group 2 – non-survivors (n = 12). Central hemodynamics was assessed through transpulmonary thermodilution. The differences were considered statistically significant at p < 0.05.Results. Most of the hemodynamic parameters and vasopressors and inotropes doses had no differences between the groups before levosimendan administration. There were no differences in the cardiac index (3.8 ± 0.3 vs 3.5 ± 0.3 L/min/m2; p = 0.479) between the groups following levosimendan administration, however, Group 1 demonstrated the following parameters to be lower versus Group 2: central venous pressure (7 ± 0.7 vs 11 ± 1 mm Hg; p = 0.005), blood lactate (1 [0.9‒1.8] vs 2.4 [2.2‒3.3] mmol/L; p = 0.04), norepinephrine dosages (0.2 [0.15‒0.35] and 0.5 [0.4‒0.6] ng/kg/min; p = 0.023 ), global end-diastolic volume index (693 [688‒28] vs 870 [779‒961] mL/m2; p =0,0009) and the level of NT-proBNP (1,590 [1,080‒3,160] vs 35,000 [21,400‒35,000] pg/mL; p = 0,0001). Global heart ejection fraction (23 [21‒27] vs 15 [12‒20]%; p = 0.015) and heart function index (6 [5‒8] vs 3 [ 3-4] min-1; p = 0.003) ) were higher in Group 1 versus Group 2. APACHE II >19 (AUC 0.906; p < 0.0001), SOFA > 9 (AUC 0.805; p = 0.0002); heart rate > 114 min-1 (AUC 0.755; p = 0.0095), and index of total peripheral vascular resistance < 1,700 dyn × s × cm-5 × m2 (AUC 0.806; p = 0.001) before levosimendan administration were the independent predictors of death in patients treated with levosimendan.Conclusion: non-survivors patients with sepsis had significantly higher APACHE II and SOFA scores, higher heart rate and lower index of total peripheral vascular resistance before levosimendan infusion. In survivors levosimendan infusion at a standard dose led to a significant improvement in the heart pumping function accompanying by global heart ejection fraction and heart function index increasing and NT-proBNP decreasing. In non-survivors such favorable central hemodynamics changes did not occur, although the cardiac index increased after inodilator administration. Further studies of levosimendan efficacy in patients with sepsis of varying severity are advisable. It is necessary to specify the indications and contraindications for levosimendan administration to patients with sepsis.